1996
DOI: 10.1007/s002689900028
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management for Carcinoid Tumors of Small Bowel, Appendix, Colon, and Rectum

Abstract: Carcinoid tumors occur most frequently in the gastrointestinal tract. Despite their ability to produce hormones, most of the midgut and hindgut carcinoids covered in this study are clinically silent, and the diagnosis is often not made before emergency surgery or evaluation for liver metastases. Because the rate of lymph node involvement and the prognosis of carcinoid tumors depend on their site and size, surgery refers to these two factors too. Lymph node metastases are most commonly found with small bowel ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
104
0
20

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(127 citation statements)
references
References 22 publications
(49 reference statements)
3
104
0
20
Order By: Relevance
“…The results of our study also confirmed the efficacy of this procedure. Only cases with tumor localization at the base of the appendix, transmural infiltration or infiltration of mesoappendix require additional therapy with right hemicolectomy or ileocecal resection [15,16] . Absolute indication for re-operation, is the existence of local lymph nodes and the existence of tumor's rupture.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study also confirmed the efficacy of this procedure. Only cases with tumor localization at the base of the appendix, transmural infiltration or infiltration of mesoappendix require additional therapy with right hemicolectomy or ileocecal resection [15,16] . Absolute indication for re-operation, is the existence of local lymph nodes and the existence of tumor's rupture.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, contrary to the older series supporting simple appendicectomy as adequate treatment (Shaw 1991), more caution is required, particularly in this young population (Roggo et al 1993, Rothmund & Kisker 1994, Stinner et al 1996. On the other hand, morbidity rates for RHC range between 17 and 37%, particularly respiratory and cardiovascular complications in the elderly (usually not the case for aNENs) or after a reoperation is performed in younger patients because of bowel occlusion (Bokey et al 1995, Alexandraki et al 2011.…”
Section: Treatmentmentioning
confidence: 99%
“…In one small retrospective study of patients with tumours !1 cm in which a simple appendicectomy was performed, no patient was found to have evidence of residual disease or recurrence after a median follow-up period of 5 years (range: 6 months-15 years) (Murray et al 2014). Several studies report metastatic rates as low as 0-1% in tumours measuring 1-2 cm as opposed to tumours O2 cm, which may develop mostly regional metastases in 20-85% (Stinner et al 1996, Stinner & Rothmund 2005, Mullen & Savarese 2011. Concerning tumour size, early studies reported that no patient with a tumour !2 cm treated with a simple appendicectomy developed recurrent or metastatic disease after a median follow-up period O26 years, while a moderate degree of local invasion was not associated with an adverse overall prognosis (Moertel et al 1987).…”
Section: Histopathological Features Used To Identify High-risk Neoplasmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are many factors correlating with increased metastatic potential, the size of the appendiceal NET is the best prognostic factor [1,3,16]. The risk of metastases in tumors less than 1 cm is near zero, and it is a matter of general agreement that appendectomy alone is justified.…”
Section: Discussionmentioning
confidence: 99%